FACTORS RELATED TO THE REGULARITY OF PREGNANT WOMEN DO ANTENATAL CARE AT KEBON JERUK HEALTH CENTER, WEST JAKARTA - Karyanah, Yayah (Indonesian Journal of Nursing Health Science, 2018)
Antenatal care is one effort to prevent maternal death by detecting early occurrence of high risk of pregnancy. This study aims to obtain a description of the factors that affect the regularity of pregnant women to do antenatal care at Kebon Jeruk Public Health Center, West Jakarta. The design of this study was descriptive with samples of third trimester pregnant women who were doing antenatal care at Kebon Jeruk Public Health Center, West Jakarta, amounted to 50 people. Technique of sampling by convinient sampling. The research is expected to find the factors that influence the regularity of pregnant women to do antenatal care, including predisposing factors including maternal age, education level, occupation and parity, knowledge. Possible factors include income, distance of residence, media informas, while the strengthening factor is the support of the husband. Statistical test using Chi Square. Result of research There is relationship between age P.value 0.026 < 0.05, parity P.value 0.044 < 0.05, knowledge P.value 0.049 < 005, attitude P.value 0.024 < 0.05, distance of residence P.value 0,037 < 0.05, support husband P .value 0.024 < 0.05 with regular antenatal care. Activeness followed high counseling 52% of the respondents, but who regularly do antenatal care hannya 22%. The need for increased counseling by the West Jakarta Health Office on antenatal care as an effort to improve the utilization of antenatal care by pregnant women.Â Keywords: antenatal care, 3rd trimester pregnant women